The Domestic Politics and Indonesia’s Tension with Malaysia on The Ambalat Case - Bustami, Reevany; Maksum, Ali (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
This study examines inter-state tension between Indonesia and Malaysia on the issue of Ambalat between 2005-2009 using quantitative analysis. The analysis offers these critical and crucial lenses to reduce empirical and conceptual blind spots in international relations discourse. The issue is pivotal since the Ambalat disputes had yielded tensions between the two nations. Furthermore, the military’s involvement and provocations of mass media were arguably excessive. Previous literature merely focuses on the foreign policy tension and neglects the correlated and critical domestic factors. The purpose of this research is expected to possess a different conceptual perspective on the issue of Ambalat, which is often framed from a security perspective. The mainstream rationale captures Ambalat as an internal political maneuver deployed by President Yudhoyono while antagonizing Indonesia’s relations with the neighbor. The analysis offers these critical and crucial lenses to reduce empirical and conceptual blind spots in international relations discourse. The results showed that President Susilo Bambang Yudhoyono (SBY) used this issue to advance specific political interests by redirecting the public’s attention from mounting petroleum costs and the president’s declining image. This also occurs against the backdrop of the presidential election of 2009 to maneuver Ambalat. However, the maneuver for the domestic audience affected Indonesia-Malaysia’s relations and the rising tension.